Effect of different levels of Scutellaria baicalensis straw on slaughter performance and rumen microorganisms of rams - Minghui Zhang; Liangzhong Hou; Yuxia Yang; Hua Zhang; Zhijun Zhang; Jinlong Li; Congbin Xu; Tongjun Guo (PLoS ONE, 2025)
The shortage of forage supply has become an issue for the development of high-quality animal husbandry. Utilizing functional diets can mitigate forage shortages while enhancing animal performance and product quality. This study aimed to investigate the effects of different levels of Scutellaria baicalensis straw (SBS) on the slaughter performance, rumen fermentation, and microbial diversity of rams. A single-factor completely randomized experimental design was adopted. Sixty 4- to 5-month-old Bainuburke rams with mean body weight of (27.08 ± 3.12) kg were randomly divided into six groups, with 10 per group. Each group received a balanced total mixed pellet diet with equivalent energy and nitrogen levels containing 0%, 6%, 12%, 18%, 24%, and 30% SBS (dry matter basis). The pre-experimental period was 10 days, followed by a 70 days formal experimental period. The results showed that: (1) Compared with the CON group, the dressing percentage and eye muscle area in the SBS24 group significantly increased (P < 0.05); (2) Compared with the CON group, the butyrate content and total fatty acid content inthe SBS24 group significantly increased (P < 0.05); (3) Compared with the CON group, the Simpson index of the SBS groups significantly increased (P < 0.05), while the Shannon index of the SBS12, SBS18, and SBS24 groups significantly decreased (P < 0.01). At the phylum level, the relative abundance of Firmicutes, Bacteroidetes, and Halobacteria increased, while the relative abundance of Proteobacteria and Actinobacteria decreased. At the genus level, the relative abundance of Prevotella, Rikenellaceae_RC9_gut_group, and Succiniclasticum increased. In summary, diets containing 6–30% SBS increased the relative abundance of Firmicutes, Bacteroidetes, and Halobacteria, while decreasing the relative abundance of Proteobacteria and Actinobacteria. This led to higher total volatile fatty acids, which in turn improved the slaughter performance of rams. Based on performance and microbiota composition, it is recommended that rams diets be supplemented with 24% SBS.